PERBEDAAN EFEKTIVITAS RENDAM AIR HANGAT DENGAN RENDAM AIR KENCUR GARAM EPSOM TERHADAP PENURUNAN EDEMA KAKI IBU HAMIL - Putri, Sekar Maharani Shila; Fajar, Ibnu; Kusmiwiyati, Ari (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2025)
Pregnant women often experience physiological discomfort in the second and third trimesters, one of which is leg edema. Leg edema that occurs in pregnant women is caused by uterine pressure which disrupts venous return and gravity which affects fluid collection. The aim of this study was to determine the effectiveness of warm water soaking versus warm water soaking with aromatic ginger and epsom salt in reduce leg edema in pregnant women in trimesters II and III at the Lawang Health Center. This study used a quasi-experimental design, with a sample of 18 pregnant women divided into two groups a control group and an intervention group, with purposive sampling technique. The data were analyzed using the Wilcoxon Signed Rank Test. The Wilcoxon test found a significant difference in the effectiveness of warm water soaking and warm water soaking with aromatic ginger and epsom salt in reducing leg edema in pregnant women in trimesters II and III (p-value = 0.008 < 0.05) At Lawang Health Center. Pregnant women find that bathing their feet in warm water with an aromatic ginger and epsom salt works better than soaking warm water to reduce foot edema. This study will motivate pregnant women and healthcare providers to create more effective treatments for reduce leg edema in pregnancy